2018
DOI: 10.1182/blood-2018-99-112295
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Curcumin and Vitamin D in Previously Untreated Patients with Early Stage Chronic Lymphocytic Leukemia (CLL) or Small Lymphocytic Lymphoma (SLL)

Abstract: B ackground: Current therapies for CLL/SLL have frequent toxicities, are non-curative, and several trials have demonstrated that early treatment of the disease doesn't result in longer overall survival. In high doses, both curcumin (CM), from turmeric, and vitamin D (VD) have been shown to be safe in multiple clinical trials of solid tumors. Curcumin was shown to disrupt CLL cell interactions with the microenvironment, induce apoptosis independent of DNA damage, and upregulate vitamin D receptor (VDR) in malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, we considered that, given the morphological variability between the lines, this assay should be performed in other leukemic lines as well as in human samples in order to confirm the absence of differentiation. Based on these initial and other more recent reports (23), future studies adding vitamin D to the AZA/CUR combination would be useful.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, we considered that, given the morphological variability between the lines, this assay should be performed in other leukemic lines as well as in human samples in order to confirm the absence of differentiation. Based on these initial and other more recent reports (23), future studies adding vitamin D to the AZA/CUR combination would be useful.…”
Section: Discussionmentioning
confidence: 94%
“…The combination of AZA and CUR has not yet been tested in hematological neoplasms, but in solid tumors a positive interaction between these drugs has been observed (21). Interestingly, CUR has also been tested in several clinical trials and proved to be safe, non-toxic and efficient as a single agent or combined with other therapies (9,22,23). Finally, although the low water solubility of CUR hinders its initial bioavailability in the bloodstream, it has recently been reported that combining it with organometallic compounds enhances significantly its transport to cancer cells (24).…”
mentioning
confidence: 99%
“…In CLL, a clinical trial carried out by the Mayo Clinic showed that vitamin D substitution in CLL patients with insufficient vitamin D levels is safe and feasible, however could not provide evidence that vitamin D can delay disease progression [ 17 ]. More recently, the combination of vitamin D with curcumin was reported to be safe in previously untreated patients with early stage CLL or small lymphocytic lymphoma (SLL), yet event-free and overall survival did not show any alteration [ 47 ]. Obviously, therefore, further studies are required in order to reach definitive conclusions regarding the role, if any, of vitamin D in the management of patients with B cell malignancies, including CLL.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Since natural supplements are complex mixtures, their net efficacy results from multiple interactions among the constituents. (2)(3)(4) Effects of natural dietary supplements have been published in various fields, such as their ability to improve in mitochondrial dysfunction. (5) Interest in natural supplements is growing, and many relevant studies are ongoing around the world.…”
mentioning
confidence: 99%
“…Several papers have reported that those natural supplements show synergism. (2)(3)(4) Jerzynska et al (3) reported that co-administration of vitamin D supplements and Lactobacillus rhamnosus showed better immunological response than individual administration in pediatric allergy rhinitis patients. These natural supplements show similar properties, but combining them can generate additive or synergistic effects on the human body.…”
mentioning
confidence: 99%